Franchise Market, Contract Conditions, and Welfare Implications: Evidence from Korea - Jinkook Lee; Myoungshik Seo (KDI Journal of Economic Policy, 2022)
This paper analyzes how franchise cont ract conditions are influenced by business structures as well as how contract conditions affect producer surplus by utilizing Korean franchise Information Disclosure Documents for the years 2014-2016. We find that franchise fees tend to increase in line with increases in the numbers of direct stores or the business period. Accordingly, it would be reasonable to check whether the franchise fee is excessive compared to the amount of reputation capital rather than to criticize the absolute level of the franchise fee. Regarding royalty contracts, the larger the discount in the raw materials purchase is, the higher the initial royalty is. Although this appears to be a royalty discount, it can be a means of inducing a raw materials purchase contract by initially setting a high royalty rate and then lowering it after the purchase contract is signed. Concerning the effect on producer surplus, the resultsshow that an increase in franchise fees and royalties negatively affects the franchisee's operating profits but positively affects those of the franchisor's, leading to conflicts over the distribution of ec onomic value added. Based on the findings here, we propose various policy recommen dations, specifically reinforcing the contents in the Information Disclosure Document, further activating fixed-rate royalties, and strengthening the qualifications of franchisors when recruiting franchisees.
Keywords: D22; L13; L16; L22; L50; 330; Korean Franchise Market; Franchise Fee; Royalty Rate; Franchise Contract Conditions